CALCULATION OF LEAF SAMPLE SIZE IN PLANTAIN HARTÓN - Ceballos Pérez, Samuel Gustavo; Rodriguez Pérez, Vianel de Jesús; Rodríguez Rodríguez, Orlando Antonio; Gómez Cárdenas, Carlos; Rodríguez Guzmán, Zulime Fatima (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to perform the monitoring or nutritional audit to cultivation Hartón plantain, two alternative sampling of leaf tissue were evaluated by: a) the preliminary completely random sample and b) stratified random sample, in order to determine the sampling frame and get the smaller sample in 2008. The analysis or experimental unit consisted of two plants, the “mother” plant at the time of inflorescence emergence and its lateral bud or “son” in full development. The leaf sample was collected according to the conditions laid down in the international reference sample (IRS). That unit was tagged with bright paint, in order to identify it at 10 to 14 weeks later and its cluster were harvested and weighed. Results showed that the sampling frame generated for stratified random sampling, allow us to determine the lowest leaf sample size in the South of Maracaibo Lake area.
Keywords: banana cluster; random; stratified sampling